Family Equivalence Scales and Personal Income Tax Exemptions for Children - Seneca, Joseph J.; Taussig, Michael K. (The Review of Economics and Statistics, 1971)
T HE normative principle of horizontal equity in personal income taxation calls for the levying of equal tax liabilities on taxpaying units enjoying identical pretax levels of economic well-being. Unfortunately, the only straightforward application of this principle is the proposition that tax-paying units identical in every other relevant respect should bear equal tax burdens if and only if they enjoy the same level of pretax money income. Economists have long recognized, of course, that the level of money income is only one of several objective factors that determine a tax-paying unit's level of economic well-being its ability to pay. Probably the foremost of the other factors is the number of individuals who must share a given total money income. Economists generally accept the principle that some system of personal exemptions, deductions, tax credits or other technical devices designed to adjust gross money income for the size of the tax-paying unit is necessary to maintain horizontal equity in personal income taxation. The purpose of this paper is to evaluate the structure of personal income tax exemptions for dependent children in the present personal income tax law against the horizontal equity standard stated above.' A review of the literature reveals that this subject has received only a sparse and elementary treatment. Public finance texts go no further than to suggest the qualitative norm that relatively large families should pay somewhat less taxes than averagesize families at a given level of gross money income. A very small number of studies take an approach which we shall pursue in greater depth-the application of a large body of work in consumption economics concerned with the determination of equivalent welfare incomes or for families that differ in size and composition to a quantitative assessment of the personal income tax exemption structure.2 Unfortunately, the direct adaptation of existing equivalence scale results is inappropriate for the purposes of tax policy, as we shall demonstrate in section II of the paper. The major contribution of this study is the estimation of a new set of equivalence scales that can legitimately be applied to the evaluation of aspects of the present tax structure that are relevant to the issue of horizontal equity. Section II of the paper briefly reviews the traditional methodology for estimating equivalence scales and then proceeds to detail the conceptual and pragmatic problems involved in adapting this methodology to our particular problem. Section III presents the statistical model for estimating our new set of equivalence scales and discusses the data source for the estimates. Section IV reports our empirical results and a final, brief section V treats the policy implications of our findings.